Using a support vector machine to determine loyalty in African, European, and North American telecoms - Mohlala, Clene; Bankole, Felix (Frontiers in Research Metrics and Analytics, 2022)
Brand loyalty is seen as a repeat purchase and the ability to recommend services or products. Telecommunication service providers require a loyal customer to stay in business. The current paper examines the impact of brand function and corporate image on customer loyalty in Telecommunication industry. The research employed a total of 971 responses from an anonymous online survey of telecommunication service providers customers in Africa, Europe, and North America. Using partial least squares, the study examined the relationships between Brand Function, Corporate Image, and Loyalty. The result shows that brand function and corporate image has a significant positive effect on customer satisfaction. In addition, a machine learning algorithm was used to model the best prediction for consumer recommendation of products and services through their telecommunication service provider to friends and famil